PENERAPAN LEAN MANUFACTURING UNTUK INDENTIFIKASI DAN MEMINIMALISIR PEMBOROSAN DI UMKM CADO AGROFOOD SEMESTA - Zakaria, Muhammad; Anshar, Khairul; Safrinanda, Safrinanda (Journal of Industrial Engineering & Management Research, 2025)
The food processing industry, especially at the Micro, Small, and Medium Enterprises (MSMEs) scale, faces challenges in increasing production process efficiency due to limited resources and suboptimal work layout. This study aims to identify and minimize waste in the chocolate bar production process at the Cado Agrofood Semesta MSME using the Lean Manufacturing approach and Value Stream Mapping (VSM) analysis tool. The research method includes collecting cycle time data, calculating standard time, takt time, and analyzing value-added and non-value-added activities. The results show that the production process still contains several types of waste, especially in waiting activities and transportation between work stations. Through the application of the Kaizen concept and redesigning the process flow (Future State Mapping), the total production time (Manufacturing Lead Time) can be reduced significantly compared to the initial condition. Proposed improvements include rearranging the work layout and controlling work time according to takt time. The application of this concept has been proven to be able to increase production efficiency and productivity at the Cado Agrofood Semesta MSME. Keywords : Lean Manufacturing, Value Stream Mapping, Kanban, Takt Time, Production Efficiency, MSME